2000
DOI: 10.1207/s15327914nc381_11
|View full text |Cite
|
Sign up to set email alerts
|

Endogenous N-Nitroso Compounds, and Their Precursors, Present in Bacon, Do Not Initiate or Promote Aberrant Crypt Foci in the Colon of Rats

Abstract: Processed meat intake is associated with increased risk of colorectal cancer. This association may be explained by the endogenous formation of N-nitroso compounds (NOC). The hypothesis that meat intake can increase fecal NOC levels and colon carcinogenesis was tested in 175 Fischer 344 rats. Initiation was assessed by the number of aberrant crypt foci (ACF) in the colon of rats 45 days after the start of a high-fat bacon-based diet. Promotion was assessed by the multiplicity of ACF (crypts per ACF) in rats giv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
1

Year Published

2004
2004
2021
2021

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 27 publications
(16 citation statements)
references
References 16 publications
0
15
1
Order By: Relevance
“…2). Fecal ATNC may not promote ACF formation (11,52) but may explain the MDF promotion observed here.…”
Section: Discussionmentioning
confidence: 58%
See 2 more Smart Citations
“…2). Fecal ATNC may not promote ACF formation (11,52) but may explain the MDF promotion observed here.…”
Section: Discussionmentioning
confidence: 58%
“…Nitrites are nitrosating agents and can interact with secondary amino compounds to form N-nitroso compounds. Parnaud et al (11,52) showed that rats fed fried bacon excrete 10 to 20 times more ATNC in feces than controls, but these ATNC do not initiate ACF in rats, nor do they promote ACF in azoxymethane-initiated rats. Haorah et al (53) showed that hotdogs contain 10 times more ATNC than fresh red meat.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…They demonstrated a dose-response increase in fecal excretion of NOCs with red meat intake, not observed with vegetable proteins, white meat or an Fe CC supplement, but clearly mimicked by a heme supplement. Also in animal studies, inclusion of red or processed red meat into the diet increased the fecal concentration of NOCs (Parnaud et al, 2000;Mirvish et al, 2003). However, the analytical method used to analyze NOCs did not differentiate between N-nitrosamines and other compounds such as Snitrosothiols, O-nitroso compounds and nitrosyl iron.…”
Section: Effect Of Heme On the Endogenous Production Of Nocmentioning
confidence: 99%
“…− is the precursor of N-nitroso compounds that have carcinogenic effect [58,59]. NO 2 − is converted into nitrous acid in acidic environment, and nitrous acids react with secondary amines to form nitrosamine compounds (Figure 2) [60].…”
Section: Nomentioning
confidence: 99%